Phone-based safety monitoring of the first year of baclofen treatment for alcohol use disorder: the BACLOPHONE cohort study protocol. Issue 2 (1st February 2017) - Rolland, Benjamin; Auffret, Marine; Labreuche, Julien; Lapeyre-Mestre, Maryse; Dib, Malek; Kemkem, Aomar; Grit, Isabelle; Drelon, Marie; Duhamel, Alain; Cabe, Nicolas; Vabret, François; Guillin, Olivier; et al.
ABSTRACT: Background: In France, baclofen is frequently used off-label for alcohol use disorder (AUD). Baclofen has been associated with diverse adverse events (AEs), but the causality of these AEs has never been properly assessed. Methods/Design: BACLOPHONE is a prospective multicenter cohort study conducted in the Hauts-de-France and Normandie French regions. BACLOPHONE consists of the phone-based monitoring of 792 patients during their first year of baclofen treatment for AUD. Two initial phone interviews assess the medical history, current medications, and substance use as well as complete the alcohol use identification test (AUDIT) and severity of alcohol dependence questionnaire (SADQ). Daily alcohol use and baclofen doses are noted throughout the follow-up. For every reported AE, additional phone interviews determine the seriousness of the AE, the causality of baclofen using validated causality algorithms, and the final outcome. The main objective of the study is to determine the rate of patients who stop baclofen due to an AE during the first year of treatment. Discussion: BACLOPHONE will provide important safety data on baclofen as a complement to the forthcoming efficacy data of randomized clinical trials.